(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Rhythmic gymnastics classes for young gymnasts are of great importance in connection with early specialization and involvement in classes of children 5-6 years old. Analysis of scientific and methodological literature shows that in recent decades, gymnastics has undergone significant changes associated with an increase in the complexity and risk of the exercises performed, on the one hand, and a sharp rejuvenation of the composition of those involved. The problem of early specialization dictates its requirements for the methodology and physical fitness of children. The introduction of rhythmic gymnastics means of the health and recreational direction is determined because rhythmic gymnastics exercises are a universal means of forming a culture of movements for children of different age categories. The use of elements of rhythmic gymnastics of the health and recreational direction for children 5-6 years old, as a means and form of organizing the physical and psychological development of the child, creates conditions for the humanization of the pedagogical process, transforming the child from an object of socio-pedagogical influence into a subject of active creative activity. We created a program for an experimental group of children 5-6 years old, which is based on the means of rhythmic gymnastics and is designed not only to increase the level of motor activity of participants in everyday life, but also to promote their physical harmonious development and positively influence the formation of their personality, which became the subject of our study. The goal of the program is to improve physical qualities and abilities, to form healthy and harmonious development of girls 5-6 years old by means of rhythmic gymnastics of the health and recreational direction. Results According to the average values obtained at the beginning and end of the experiment, it can be seen that there was an improvement in speed-strength and coordination abilities, the level of flexibility and mobility in the joints. According to the program we developed, we can note its effective impact on the physical fitness and harmonious development of girls aged 5-6.